ANALISIS YURIDIS KEDUDUKAN HUKUM KARYAWAN DALAM MENGAJUKAN PERMOHONAN PKPU TERHADAP DEBITOR DI PENGADILAN NIAGA - Muhammad Thaufik Saragih; Widodo Ramadhana (Jurnal Hukum Lex Generalis, 2024)
This study aims to understand the regulations regarding PKPU applications according to the Bankruptcy and PKPU Laws, this is related to understanding the legal basis for submitting PKPU applications, both by Debtors and Creditors in accordance with the laws and regulations in Indonesia and to know and understand the position of employees as preferred creditors in PKPU applications at the Commercial Court. This study uses a normative legal approach with an approach to statutory regulations. This normative legal research is based on the interpretation of laws, court decisions, and other relevant legal documents.